1996
DOI: 10.1063/1.116625
|View full text |Cite
|
Sign up to set email alerts
|

Superconductor-normal-superconductor behavior of Josephson junctions scribed in Y1Ba2Cu3O7−δ by a high-brightness electron source

Abstract: We report a substantial improvement in the behavior of Josephson junctions scribed in Y1Ba2Cu3O7−δ films using a high-brightness field-emission electron gun source instead of a lower-brightness thermionic source. These junctions exhibit resistively shunted junction behavior over the entire temperature range from the coupling temperature to at least 4 K, a temperature window which can be larger than 55 K. Superconductor-normal-superconductor character is indicated by the exponential dependence of the critical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…INTRODUCTION reliable high temperature superconductor (HTS) junction fabrication technology for large-scale integration has been a long-standing requirement. One of the candidate technologies, at least in terms of junction quality and reproducibility, is the focused electron beam irradiation technique (FEBI) developed in Cambridge and elsewhere [1,2] in which the superconducting transition temperature (T c ) is locally suppressed by irradiation-induced damage. It was realized early on that much of the electron-induced damage is unstable at room temperature, and so the properties of early junctions changed rapidly with time.…”
Section: Index Terms-superconducting Devices Nanotechnology Ybco Snmentioning
confidence: 99%
“…INTRODUCTION reliable high temperature superconductor (HTS) junction fabrication technology for large-scale integration has been a long-standing requirement. One of the candidate technologies, at least in terms of junction quality and reproducibility, is the focused electron beam irradiation technique (FEBI) developed in Cambridge and elsewhere [1,2] in which the superconducting transition temperature (T c ) is locally suppressed by irradiation-induced damage. It was realized early on that much of the electron-induced damage is unstable at room temperature, and so the properties of early junctions changed rapidly with time.…”
Section: Index Terms-superconducting Devices Nanotechnology Ybco Snmentioning
confidence: 99%
“…To realize the practical high-transition temperature (high-) SQUIDs, various junctions technologies have been developed, including bicrystal, step-edge, ramp-edge, interface-modified, biepitaxial, step-edge superconductor-normal-superconductor, and locally damaged junctions [1]- [5]. Many efforts have been made to improve the junction fabrication technology to increase the reliability of fabrication and the reproducibility of junction parameters [4], [5]. The bicrystal grain boundary junctions have achieved excellent critical current and normal resistance product with acceptable reproducibility [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Several groups 8,9 have shown that HTS films in which a narrow barrier with reduced T c has been created by focused electron-beam irradiation can display the Josephson effect in a limited temperature range below the electrode T c . The absence of cation disorder in these barriers makes them excellent candidates for interpreting the Josephson effect in HTS structures if the barrier properties can be quantified.…”
mentioning
confidence: 99%
“…9 The samples were patterned for four-point measurements of four 2.5 m-wide by 10 mlong links per substrate, with twelve contact pads on the perimeter of the disk. A small slot cut in each substrate permitted in situ focusing and alignment of the electron beam.…”
mentioning
confidence: 99%
See 1 more Smart Citation